2020
DOI: 10.1089/vim.2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Porcine Pseudorabies Virus and Its Coinfection Rate in Heilongjiang Province in China from 2013 to 2018

Abstract: Pseudorabies (PR) is a highly contagious disease affecting a wide range of animals, which annually causes great economic losses in China. In this study, a total number of 18,815 serum samples and 1,589 tissue samples were collected from 311 intensive pig farms (‡350 sows) located in eight cities in Heilongjiang province, and tested by ELISA and PCR. Overall, the serum positive rates of gE and gB protein were 16.3% and 84.5%, respectively. The PCR-positive rate of PR virus (PRV) in tissue samples was 17.8%. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
(26 reference statements)
2
18
1
Order By: Relevance
“…The variable temperature in autumn may partially state this result, and similar results were also reported in a previous study ( 17 ). Meanwhile, as reported in Zhou's study ( 21 ), the lowest PRV seroprevalence was also observed in fattening pigs, which might be associated with the limited breeding time.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The variable temperature in autumn may partially state this result, and similar results were also reported in a previous study ( 17 ). Meanwhile, as reported in Zhou's study ( 21 ), the lowest PRV seroprevalence was also observed in fattening pigs, which might be associated with the limited breeding time.…”
Section: Discussionsupporting
confidence: 61%
“…PRV prevalence in pigs varied in different regions in China. In Henan province, 30.14% (1,419/4,708) of samples collected during 2018–2019 were gE-seropositive ( 17 ), while the serum gE-positive rate was 16.3% (3,067/18,815) in Heilongjiang province from 2013 to 2018 ( 21 ). All data indicate that seroprevalence of variant PRV is still high in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a highly neurovirulent PRV strain was recently isolated from pigs vaccinated with PRV Bartha K-61 [15,16]. Notably, the Bartha K-61 vaccine does not protect the vaccinated pigs clinically against the neurovirulent PRV strain [15][16][17][18]65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Since PCV2, CSFV, and PRV are endemic, and co-infections are common in intensive pig farms in China [17], the severity and fatality of the disease and the emergence of a highly pathogenic PRV strain could have been the result of complex epidemiological interactions between the PRV and co-infecting virus(es) [18]. Both CSFV and PRV have been eradicated in the US and many European countries.…”
Section: Introductionmentioning
confidence: 99%